A STUDY ON YOUNG LEARNERS’ VOCABULARY MASTERY AT ELEMENTARY SCHOOL - Vischa Mansyera Pratama; Ramanda Rizky (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research aims to analyze of the students’ vocabulary mastery of the fourth grade students of SDN 15 Padang Sarai. The research design is descriptive qualitative method. The study sample is 32 students. The result of data analysis showed that vocabulary test can be conducted to young learners to assess students’ vocabulary mastery. The conclusion to the classification of category is poor to very good which mean that vocabulary of the fourth grade of SDN 15 Padang Sarai is in good level for achievement in English lesson in mastering vocabulary. It is found that 41% students at good level, 37% at very good level, 16% is fair, and 6% at poor level. The author suggests that English teacher should have particular techniques to teach vocabulary for example the teacher can use the real object to show the meaning of the words, in order to make the students easier in mastering vocabulary and learning English subject.